Effectiveness of Plasma Activated Water Generated by AC Gliding Arc Discharge for Bacterial Inactivation on Strawberries - Dhungana, Santosh; Karki, Rajan; Singh, Akhilesh Kumar; Subedi, Deepak Prasad; Khanal, Raju; Baniya, Hom Bahadur (Amrit Research Journal, 2025)
This study investigates the effectiveness of plasma-activated water (PAW), generated using an AC gliding arc discharge (GAD) system, for bacterial inactivation on strawberries. The discharge was produced in air between divergent aluminum electrodes powered by 7–10.1 kV at 50 Hz. Optical emission spectroscopy revealed the presence of reactive species such as OH, NOx, N2, and N2+, confirming the generation of reactive oxygen and nitrogen species (RONS) crucial for antimicrobial activity. Physical characterization of PAW showed a significant decrease in pH (from 6.8 to 4.06), an increase in oxidation reduction potential (from 300 mV to 420 mV) and conductivity (up to 71.33 μS/cm) with increasing applied voltage, indicating enhanced reactivity. The antibacterial efficacy of PAW was evaluated by washing strawberry samples with plasma-treated and untreated water. After 24 hours of incubation, the bacterial colony count for strawberries washed with plasma-treated distilled water decreased from 1100 to 34 CFU/mL. This result demonstrates that PAW generated by AC gliding arc discharge effectively reduces bacterial contamination on strawberries, offering a safe, chemical-free, and sustainable approach for food sterilization and preservation.